Design and development of a quadruped home surveillance robot - Owoeye, Samuel Oluyemi; Durodola, Folasade; Adeniyi, Peace Oluwafeyidabira; Abdullahi, Idris Tolulope; Hector, Adesanya Boluwatito (IAES International Journal of Robotics and Automation (IJRA), 2024)
Quadruped home surveillance robots represent a promising advancement in home security and automation. This innovative robotic system is equipped with four-legged locomotion, allowing it to traverse various terrains within a household environment. The robot's primary function is surveillance, and it is equipped with high-definition cameras, motion sensors, and object recognition software. These sensors enable the robot to detect intruders, track their movements, and capture real-time video footage for remote monitoring. The quadruped robot's compact and agile design allows it to navigate through narrow spaces and overcome obstacles, ensuring it can patrol every corner of a home effectively. Its autonomous operation is made possible through advanced artificial intelligence algorithms, ensuring that it can detect anomalies and respond to security threats promptly. Furthermore, integrating the robot with smart home systems enables seamless communication with other connected devices and allows homeowners to control and monitor it remotely.